The Motivational Factors Among Undergraduates Learning Mandarin In A Higher Education Institution - Cheong, Kar Mee; Jano, Zanariah; Yahya, Aziz; Hussin, Hanipah (Scottish Journal of Arts, Social Sciences and Scientific Studies (SJASS)., 2013)
Today, Mandarin is considered an increasingly important international language. Many high schools and universities in many countries throughout the world offer Mandarin as a foreign language.The purpose of this study was to investigate the motivational factors of undergraduate students learning Mandarin as a foreign language at Universiti Teknikal Malaysia Melaka (UTeM). A quantitative analysis was used through motivation inventory as a survey instrument. It involved 147 undergraduate students who were learning Mandarin as a foreign language at UTeM. The findings have shown that future occupation is a major motivational factor for a student to learn Mandarin at UTeM followed by intrinsic value and self-development. The results is important in determining the content of Mandarin learning material. In future more research in different learning contexts should be considered for a deeper understanding of motivation in Mandarin as well as other foreign language learning.